Membangun Lingkungan Literasi melalui Pojok Baca di MA Darul Ulum Palangka Raya - Sidqi, Ansori; Supriadi, Gito; Hasanah, Nor (Al-DYAS, 2025)
This community service initiative is grounded in the importance of strengthening literacy culture as a foundation for improving the quality of education in madrasah. The primary objective of the activity was to establish a pojok baca (reading corner) as a strategic facility to support literacy at MA Darul Ulum Palangka Raya. A participatory-collaborative method was employed, involving students, teachers, and learners throughout all stages—ranging from literacy needs assessment, planning, and implementation to evaluation. The reading corner was designed not only as a space for reading but also enhanced with religiously inspired motivational quotes to foster enthusiasm and reinforce the Islamic identity of the madrasah. The results indicated a positive response from students, reflected in increased reading enthusiasm and the emergence of a more conducive academic atmosphere. Collaboration among stakeholders further supported the sustainability of the program, demonstrating a significant impact on enhancing literacy culture and educational quality within the madrasah. The initiative concludes that simple innovations such as the reading corner can serve as an inspirational model for other educational institutions in building a sustainable and contextually relevant literacy ecosystem.